Neural crest cell recruitment and reprogramming as central drivers of embryonic limb regeneration - Béryl Laplace-Builhé; Gautier Tejedor; Jholy De La Cruz; Audrey Barthelaix; Frédéric Marmigère; Dora Sapède; Sarah Bahraoui; Lucie Diouloufet; Stéphanie Ventéo; Jérôme Collignon; Christian Jorgensen; Farida Djouad (Proceedings of the National Academy of Sciences, 2025)
Unlike regeneration-competent species, mammals lack epimorphic regeneration capacity, except for the most distal part of their digits. Here, we show that E10.5 mouse embryos can initiate regeneration of their forelimb bud (FB), but this capacity is lost by E12.5. Using comparative transcriptomics and in vivo lineage tracing approaches in the mouse embryo, we were able to identify a population of neural crest–derived cells (NCdCs) reexpressing early NC lineage molecular markers, Wnt1 and Foxd3 , specifically associated with regeneration at E10.5. Functional studies further reveal that these cells are required for FB regeneration and that the regenerative capacity lost in limb buds lacking NCdCs can be restored by exogenous transplantation of neural crest cells at E10.5. This work provides valuable information on the potential and prerequisites for regeneration in mammals.